The "last thought is to escape": New Zealand’s tree-planting prison camps - McCarthy, Christine (Architectural History Aotearoa, 2022)
1913 marked the close of New Zealand’s first prison tree-planting camp (Waiotapu). The 1910s also saw the closure of the Hanmer and Waipa Valley camps. Dumgree was the first to close in 1908 and Kaingaroa the last in 1920. Tree-planting also occurred at Point Halswell from 1904 continuing through the 1910s, resulting in the forestation of Miramar Peninsular with over 160,000 trees having been planted by 1915. Tree-planting, like other work camps, were considered to be suitable for only some prisoners, with Hume stating that: "Some men are safe only under lock and key and behind a fourteen-foot boundary-wall. The class of prisoner required for tree-planting or similar work in the country is the man who is determined to shorten his term of imprisonment by good conduct and industry, whose last thought is to escape, and who therefore needs little supervision." Additionally, tree-planting camps reflected late nineteenth-century shifts in criminology, which emphasised individual pyschology (over physical punishment), in both the selection of inmates suitable for tree-planting and the potential for behavioural change. This paper will examine this period of New Zealand’s tree-planting prison camps.